VALVULAR HEART DISEASES: AN INSIGHT THROUGH AYURVEDA - Amit Kumar, Deepshikha, Rai (International Journal of Ayurveda and Pharma Research, 2015)
Cardiovascular diseases have a large share amongst non-communicable diseases. Valvular heart diseases constitute a significant part of cardiovascular diseases which cause morbidity and mortality in India. India is currently heading towards becoming a heart disease capital of world. This puts a tremendous pressure on available resources of medical and surgical management. Thus, it would be a great asset if these diseases could be managed through traditional systems of medicine like Ayurveda, which would prove to be a good conventional treatment and prevent the development of complications and need for surgery. This article aims at understanding of VHD (Valvular heart diseases) through an Ayurvedic perspective and critically analyzes the treatment options in Ayurveda. It is noticed that though no single disease can be directly correlated to VHD, many of the clinical features of Hrida roga mentioned in Ayurvedic classics are similar to that of VHD and can be adequately managed by classical herbs and formulations.